Use of Antidepressant Medications Moderates the Relationship Between Depressive Symptoms and Hospital Length of Stay in Patients with Advanced Cancer. (6th August 2018) - Wong, Risa L.; El‐Jawahri, Areej; D'Arpino, Sara M.; Fuh, Charn‐Xin; Johnson, P. Connor; Lage, Daniel E.; Irwin, Kelly E.; Pirl, William F.; Traeger, Lara; Cashavelly, Barbara J.; Jackson, Vicki A.; Greer, Joseph A.; et al.
Abstract: Background: Among patients with cancer, depressive symptoms are associated with worse clinical outcomes, including greater health care utilization. As use of antidepressant medications can improve depressive symptoms, we sought to examine relationships among depressive symptoms, antidepressant medications, and hospital length of stay (LOS) in patients with advanced cancer. Materials and Methods: From September 2014 to May 2016, we prospectively enrolled patients with advanced cancer who had an unplanned hospitalization. We performed chart review to obtain information regarding documented depressive symptoms in the 3 months prior to admission and use of antidepressant medications at the time of admission. We compared differences in hospital LOS by presence or absence of depressive symptoms and used adjusted linear regression to examine if antidepressant medications moderated these outcomes. Results: Of 1, 036 patients, 126 (12.2%) had depressive symptoms documented prior to admission, and 288 (27.8%) were taking antidepressant medications at the time of admission. Patients with depressive symptoms experienced longer hospital LOS (7.25 vs. 6.13 days; p = .036). Use of antidepressant medications moderated this relationship; among patients not on antidepressant medications, depressive symptoms were associated with longer hospital LOS (7.88 vs. 6.11 days; p = .025), but among those on antidepressant medications, depressive symptoms were not associated with hospital LOS (6.57 vs. 6.17 days; p = .578). Conclusion: Documented depressive symptoms prior to hospital admission were associated with longer hospital LOS. This effect was restricted to patients not on antidepressant medications. Future studies are needed to investigate if use of antidepressant medications decreases LOS for patients hospitalized with advanced cancer and the mechanisms by which this may occur. Implications for Practice: This study investigated the prevalence of documented depressive symptoms in patients with advanced cancer in the 3 months prior to an unplanned hospitalization and the prevalence of use of antidepressant medications at time of hospital admission. The relationship of these variables with hospital length of stay was also examined, and it was found that documented depressive symptoms were associated with prolonged hospital length of stay. Interestingly, antidepressant medications moderated the relationship between depressive symptoms and hospital length of stay. These findings support the need to recognize and address depressive symptoms among patients with advanced cancer, with potential implications for optimizing health care utilization. Abstract : Patients with cancer often experience depression, which can influence treatment outcomes and quality of life. This article evaluates associations among depressive symptoms, use of antidepressants, and hospital length of stay in patients with advanced cancer.